Research on spatial reasoning in mathematics education: Trend and opportunity - Palupi, Evangelista LW; Juniati, Dwi; Khabibah, Siti (Universitas Maritim Raja Ali Haji, 2023)
Spatial thinking is important in learning Science, Technology, Engineering, and Mathematics. Numerous studies about spatial ability in various fields like mathematics, neuroscience and phycologist considered various factors such as gender, age, or demography. However, a few studies are still about enhancing spatial ability in the context of mediated pedagogies. This study aims to describe spatial research on mathematics education, especially related to the intervention or learning design of spatial reasoning. A bibliometric study is employed to determine the research trend of spatial reasoning, especially related to teaching practice. The review follows a structured design consisting of several stages of the PRISMA method. From 652 documents about spatial in mathematics education gathered from the Scopus data, it is reduced to 40 documents regarding spatial reasoning in mathematics education. Further, only 19 documents about intervention and practice in enhancing spatial reasoning exist. This study may benefit researchers in mathematics education by showing the development and trend of spatial reasoning research and suggesting new directions for future research.